The Comparison Between Non-High Risk Patients with and Without Cancer Diagnosed with Pulmonary Embolism - Caliskan, Tayfun (Medeni Med J, 2021)
OBJECTIVE: This study aimed to compare the pulmonary embolism (PE) location and clot burden on computed tomography pulmonary angiography (CTPA), the degree of right ventricular dysfunction (RVD), D-dimer, and cardiac troponin I (cTnI) levels, and the presence of a lower extremity deep venous thrombosis (DVT) in patients with and without cancer diagnosed with a non high risk pulmonary embolism (PE). METHOD: We calculated Miller score for each patient for clot burden. The location of PE was also evaluated at CTPA. D-dimer and cardiac cTnI levels were measured. Patients had echocardiography for RVD and lower extremity color flow Doppler ultrasonography for DVT. RESULTS: The study included 71 patients with PE. The patients were divided into two groups according to the presence of cancer. There was no statistically significant difference for D-dimer levels (P=0.15), PE location (p=0.67), clot burden (P=0.34), RVD (P=0.28) and DVT (P=0.33) between groups (P=0.15). Cancer patients diagnosed as PE had statistically significantly higher levels of cTnI than those who were diagnosed as PE without cancer (P=0.03). CONCLUSION: There was no significant difference between patients diagnosed as PE with and without cancer in terms of D-dimer levels, clot burden and emboli location, RVD and DVT. cTnI levels were higher in non-high risk PE patients with cancer than these patients without cancer.